Ramona's world [compact disc, unabridged] - Cleary, Beverly (HarperCollins Childrens, 2010)
Ramona Quimby is ready to start the fourth grade, even though her spelling could use a bit of work. Despite her woes, she has written a pretty good essay about her new baby sister. She even has a new friend named Daisy. But along with her spelling, there are many challenges and adventures ahead for Ramona as the year goes on.